Pricing of ACT/ATM services through Bilevel programming approaches - Guettaf, Rabah; Mancel, Catherine; Larbani, Moussa; Mora-Camino, Felix (Brazilian Air Transportation Research Society, 2010)
In this study a multilevel framework is proposed to analyze the charges definition problem for an ATC/ATM service provider. Two cases are considered: a case in which the ATC/ATM service provider is a public company whose final objective is, while guaranteeing safety, to promote the level of end users demand, and a case in which the ATC/ATM service provider is a private company whose objective is to maximize her profit. In both cases this leads to the formulation of a bi-level optimization program involving the ATC/ATM service provider as the leader and the whole airline sector as the follower. Direct optimal solutions are obtained in the simplistic considered one dimensional case. Then in both cases, public or private, natural negotiation schemes between the ATC/ATM service provider and the airline sector are introduced. Sufficient conditions are established so that the proposed negotiation processes converge towards the respective optimal solutions while a compensation scheme is proposed to make the two solutions identical. This study provides a basis for the study of the ATC/ATM charge definition problem for more complex airspace market structures.